Deference, Authority, and Administrative Review - Phillips, John-Otto K. (My University, 2012)
Canadian courts have struggled to develop a consistent and coherent approach for reviewing administrative decision-making. In particular, they have been unable to create a workable framework that will guide when the courts will show deference to administrative tribunal interpretations of law and when they will interfere with them, leading to a system of administrative law that is unpredictable and disorderly. This thesis develops a novel approach to administrative review centered on a conception of judicial due-deference that is correlated with a Razian account of legitimate authority. My argument is that administrative review is best understood as an exercise of inter-institutional decision-making in which diverse institutions within the meta-institution of government must work together to arrive at decisions that best secure government objectives. When reviewing courts recognize that administrative actors are better situated in particular circumstances to make decisions than the courts, they ought to show deference. On the other hand, when courts are better situated to handle these matters, deference is not to be shown. I begin in Part I by analyzing the history of Canadian administrative law jurisprudence through to the Supreme Court’s 2008 decision in Dunsmuir, highlighting the competing principles of the rule of law and democracy that animate the ‘Diceyan Dialectic’. In Part II, I articulate a complex theory of inter-institutional reasoning that demonstrates the important role of deference and authority in good government decision-making. In Part III, I apply this model to the circumstances of Canadian administrative review. I show how there are certain institutional strengths, as well as key limitations, with respect to how our superior courts can play a role in upholding the Rule of Law and democracy. Ultimately, I argue that the superior courts must pay attention to the unique institutional placement of administrative actors relative to them in order to discern if these non-curial actors possess greater authority and hence ought to be shown deference.
Keywords: judicial review; administrative law; judicial deference; administrative tribunals; legal philosophy; judicial restraint; Administrative Law; Constitutional Law; Ethics and Political Philosophy; Judges; Jurisdiction; Jurisprudence; Political Theory; Public Administration; Public Law and Legal Theory; Rule of Law; Administrative Law